A measure of success : Protestants and public culture in antebellum Cleveland - McTighe, Michael J., 1948- (State University of New York Press, 1994)
This book examines the role Protestants played in the formation of the public culture of antebellum Cleveland, a developing commercial city typical of many cities throughout the Midwest. The author analyzes the extent to which, and the way in which, Protestants were able to exercise power in the city, concluding that they achieved a measure of success during the years 1836 to 1860, after which their power began to erode.